Solving distributed two-stage hybrid flowshop scheduling using a shuffled frog-leaping algorithm with memeplex grouping. Issue 9 (1st September 2020) - Lei, Deming; Wang, Tian
Abstract : Two-stage hybrid flowshop scheduling in a single factory has been considered fully; however, the distributed two-stage hybrid flowshop scheduling problem (DTHFSP) is seldom studied in a multi-factory environment. In this study, a DTHFSP with sequence-dependent setup times is investigated and a shuffled frog-leaping algorithm with memeplex grouping (MGSFLA) is proposed to minimize makespan and the number of tardy jobs. After an initial population is generated by an heuristic, two phases are executed sequentially with a new population division. In the second phase, all memeplexes are categorized into three groups, the different search processes are implemented in the different groups and the best memeplex is excluded from population division. A number of experiments are conducted on many instances and computational results validate the effectiveness of the main strategies and the promising advantages of an MGSFLA.